(untitled) - Shaxson, Francis (Rome, 2003)
This publication discusses the processes above, within and below the soil that enable water to move and crops to grow, and is intended to help land users make better use and take better care of these basic resources. It aims to provide a solid basis for sound, sustainable soil moisture management. This document has been made more user-friendly by presenting a guide for field workers with activities, exercises and discussion topics in non-technical language, and by interspersing the text with illustrations and diagrams. The complete materials of this guide are included on the CD-ROM that accompanies this document
Keywords: Plant-soil relationships,Plant-water relationships,Soil moisture,Plants; Effect of soil moisture on